Conventional and non-conventional experimental techniques for evaluating the properties of construction materials - Ahed Habib; Ausamah AL Houri; Salah Al-Toubat; M. Talha Junaid (Discover Civil Engineering)
Abstract The evaluation of construction materials is crucial for the development of sustainable and resilient infrastructure, ensuring that materials can withstand diverse environmental conditions and stresses. Despite significant advances in material science and numerical modeling, experimental testing remains essential for a comprehensive understanding of material properties. This study provides a thorough review of both conventional and innovative experimental techniques used to characterize construction materials, with a focus on mechanical, chemical, thermal, microstructural, durability, physical, and rheological properties. By examining methods such as mechanical strength tests, spectroscopy, thermogravimetric analysis, and non-destructive testing, the study highlights the strengths, limitations, and practical applications of these approaches within the industry. The review also identifies critical gaps in the application of advanced testing techniques and underscores the need for standardized protocols to enhance the reliability and comparability of results. This work aims to inform future research and industry practices, promoting the development of more effective and sustainable construction materials.